2021
DOI: 10.1111/hepr.13592
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of efficacy of lenvatinib treatment in highly advanced hepatocellular carcinoma with tumor thrombus in the main trunk of the portal vein or tumor with more than 50% liver occupation: A multicenter analysis

Abstract: Aims To assess the safety, efficacy, and prognostic impact of clinical factors associated with lenvatinib treatment in highly advanced hepatocellular carcinoma (HCC) with tumor thrombus in the main portal vein trunk (VP4) or tumor with more than 50% liver occupation (tm50%LO). Methods A total of 61 highly advanced HCC patients (41 patients with tm50%LO and 20 patients with VP4) who were treated with lenvatinib at multicenter were enrolled and retrospectively analyzed for treatment outcomes according to their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Lenvatinib has been approved for first-line treatment of patients with unresectable advanced HCC in many countries. The safety and efficacy of lenvatinib for HCC patients has been demonstrated in clinical practice in many studies ( Chuma et al, 2020 ; Han et al, 2020 ). Since 2018, lenvatinib has become another first-line systemic treatment for HCC patients and is deemed an alternative to sorafenib due to its comparable efficacy ( Kudo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lenvatinib has been approved for first-line treatment of patients with unresectable advanced HCC in many countries. The safety and efficacy of lenvatinib for HCC patients has been demonstrated in clinical practice in many studies ( Chuma et al, 2020 ; Han et al, 2020 ). Since 2018, lenvatinib has become another first-line systemic treatment for HCC patients and is deemed an alternative to sorafenib due to its comparable efficacy ( Kudo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the REFLECT trial, the multikinase inhibitor lenvatinib 9 was not inferior to sorafenib with respect to OS. The results of these clinical trials have been confirmed in numerous real‐world studies 10–14 …”
Section: Introductionmentioning
confidence: 64%
“…Notably, the REFLECT trial excluded patients with adverse prognostic tumor characteristics, such as main branch portal vein thrombosis or greater than 50% tumor occupation of the liver, which are commonly seen in advanced stage and nearly unavoidable in routine clinical decision making. Recent studies have found that Lenvatinib also offered a survival benefit in patients with highly advanced HCC and may lead to more favorable outcomes compared with Sorafenib[ 16 - 18 ]. Approval for Lenvatinib was granted by the Food and Drug Administration (FDA) as the first-line agent, and it was included in the latest BCLC and EASL guidelines[ 1 , 3 ].…”
Section: Systemic Therapymentioning
confidence: 99%